PROFIL FITOKIMIA EKSTRAK ETANOL DAUN ANTING – ANTING (ACALYPHA INDICA LINN) DI KOTA KUPANG, NTT - Laut, Meity Marviana; Ndaong, Nemay; Amalo, Filphin; Toha, Larry; Deta, Herlina Umbu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Acalypha indica Linn is a tropical weed, grows annually in East Nusa Tenggara. The weed is member of Euphorbiaceae family, a largest plant family known as medicinal plant. The weed leaves were used by local people in NTT to treat wounds, diseases or myasis on their livestock. This study aim to investigate the secondary metabolites in A. indica L leaves as a scientific proven for its local use. The extract preparation comprises of several steps, i.e collection of fresh leaves, dry and wet sortation. The clean leaves were air dried in a room temperature for about 2 weeks before grounded into powder and subjected to extraction. The extraction method was maceration with ethanol 96% as solvent. The dense extract was evaporated using rotary evaporator and subjected to phytochemical screening. The result shows that ethanol extract of A.indica leaves were tested positive for flavonoid and tannin. Alkaloid, saponins, triterpenes and steroid were tested negative on the extract.